2003
DOI: 10.1242/dev.00628
|View full text |Cite
|
Sign up to set email alerts
|

The role ofSix1in mammalian auditory system development

Abstract: The homeobox Six genes, homologues to Drosophila sine oculis(so) gene, are expressed in multiple organs during mammalian development. However, their roles during auditory system development have not been studied. We report that Six1 is required for mouse auditory system development. During inner ear development, Six1 expression was first detected in the ventral region of the otic pit and later is restricted to the middle and ventral otic vesicle within which, respectively, the vestibular and auditory epithelia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

19
405
0
1

Year Published

2003
2003
2019
2019

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 317 publications
(425 citation statements)
references
References 50 publications
19
405
0
1
Order By: Relevance
“…Indeed, our previous studies in tissue culture cells have demonstrated that Six1 overexpression can alter progression through S phase and also through G 2 /M (Ford et al, 1998;Coletta et al, 2004), times when Six1 activity would be expected to be high. Furthermore, a number of knockout studies in mice have demonstrated a critical role for Six1 in the proliferation of precursor cell populations, leaving no ambiguity about the importance of Six1 in proliferation in vivo (Zheng et al, 2003;Ozaki et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, our previous studies in tissue culture cells have demonstrated that Six1 overexpression can alter progression through S phase and also through G 2 /M (Ford et al, 1998;Coletta et al, 2004), times when Six1 activity would be expected to be high. Furthermore, a number of knockout studies in mice have demonstrated a critical role for Six1 in the proliferation of precursor cell populations, leaving no ambiguity about the importance of Six1 in proliferation in vivo (Zheng et al, 2003;Ozaki et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…(Li et al, 2003;Zheng et al, 2003;Ozaki et al, 2004). Gene amplification and overexpression of Six1 is observed in human cancers, where it confers developmental properties on adult cells leading to an increase in both proliferation and metastasis (Li et al, 2002;Coletta et al, 2004;Reichenberger et al, 2005;Yu et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Mutations in SIX1 and EYA1 were identified in human patients with branchio-oto-renal (BOR) syndrome, which is characterized by craniofacial abnormalities, hearing loss, and kidney defects (39,40). Six1-or Eya1-deficient mice showed increased apoptosis in the inner ear and kidney, likely causing a lack of inner ear structure and failure of kidney development (32,42,43). In these mice, increased or decreased apoptosis is seen in tissues in which abnormalities also are observed in human HPE or BOR patients.…”
Section: Human Diseases Caused By Mutations In Six Family Homeodomainmentioning
confidence: 99%
“…L'analyse des marqueurs myogéniques exprimés chez ces souris a permis d'établir le rôle tardif de Six1 au cours de la myogenèse primaire (Figure 2). Six1 participe également à l'organogenèse rénale et thymique, à la morphogenèse du squelette craniofacial et thoracique, ainsi qu'à la différenciation de l'oreille interne, de la cavité nasale et des glandes lacrymales et parotides [27][28][29][30]. Comme la plupart de ces défauts sont comparables à ceux décrits chez les souris dont le gène Eya1 a été invalidé (Figure 3) [31,32], il est probable que Six1 et Eya1 agissent en synergie pour induire le développement de ces organes selon un mécanisme similaire à celui mis en évidence chez la drosophile au cours de l'organogenèse oculaire.…”
Section: Six1/six2unclassified